Expanding co-payment for methadone maintenance services in Vietnam: the importance of addressing health and socioeconomic inequalities - Bach Xuan Tran; Quyen Le Nguyen; Long Hoang Nguyen; Huong Thu Thi Phan; Huong Thi Le; Tho Dinh Tran; Thuc Thi Minh Vu; Carl A. Latkin (BMC, 2017)
Abstract Background Ensuring high enrollment while mobilizing resources through co-payment services is critical to the success of the methadone maintenance treatment (MMT) program in Vietnam. This study assessed the willingness of patients to pay (WTP) for different MMT services delivery models and determined its associated factors. Methods A facility based survey was conducted among 1016 MMT patients (98.7% male, 42% aged 35 or less, and 67% living with spouse) in five MMT clinics in Hanoi and Nam Dinh province in 2013. Socioeconomic, HIV and health status, history of drug use and rehabilitation, and MMT experience were interviewed. WTP was assessed using contingent valuation method, including a set of double-bounded binary questions and a follow-up open-ended question. Point and interval data models were used to estimate maximum willingness to pay. Results 95.5% patients were willing to pay for MMT at the monthly mean price of US$ 32 (95%CI = 28-35). Higher WTP was associated with higher level of educational attainment, higher income, male sex, and had high expenses on opiates prior to MMT. Patients who reported having any problem in Pain/ Discomfort, and who did not have outpatient care last year were willing to pay less for MMT than others. Conclusion High level of WTP supports the co-payment policies as a strategy to mobilize resources for the MMT program in Vietnam. However, it is necessary to ensure equalities across patient groups by acknowledging socioeconomic status of different settings and providing financial supports for disadvantaged patients with severe health status.